Efficiency of biological control for protecting potatoes against the Colorado potato beetle in the Western Forest-Steppe region of Ukraine - Solomiychuk, M.P.; Pikovskyi, M.Y.; Gavriluck, A.T.; Semenchuk, V.H. (Quarantine and plant protection, 2026)
Goal. To investigate the efficiency of biological control schemes based on biological preparations from ITI ‘Biotechnika’ against the Colorado potato beetle on potatoes in the Western Forest-Steppe of Ukraine. Methods. Laboratory (pest identification) and field (analysis of growth parameters) studies. Six control schemes were investigated. Results. Treatments 2 and 6 showed the best results against the Colorado potato beetle. Scheme 2: first treatment — Bitoxibacillin BT, SC (cells of the bacterium Bacillus thuringiensis var. thuringiensis, exospores, endospores, titre 2 × 10⁹ CFU/cm³), 3.0 l/ ha, second treatment — Metarhizine BT, SC (cells of the fungus Metarhizium anisopliae, titre 2.0 × 10⁹ CFU/cm³), 3.0 l/ ha, third treatment — Beauverin BT, SC (cells of the fungus Beauveria bassiana, titer 3.0 × 10⁹ CFU/cm³), 10.0 l/ha, fourth treatment — Actofit BT (cells of the fungus Streptomyces avermitilis, titer 1.0 × 10⁹ — 2.0 × 10⁹ CFU/cm³), 3.0 l/ ha). Scheme 6: first treatment — Bitoxibacillin BT, SC, 3.0 l/ha, second treatment — Boverin BT, SC, 10.0 l/ ha, third treatment — Actofit BT, SC, 3.0 l/ ha, fourth treatment — Metarizin BT, SC, 3.0 l/ha. The efficacy of scheme 2 was 70.1%, and that of scheme 6 was 71.7%. Biological protection schemes 2, 4 and 6 had a positive effect on structural yield indicators: the average tuber weight and the quantity of marketable and seed potatoes increased. The highest yield was obtained with biological protection scheme 6. Conclusions. The use of biological insecticides helped to maintain potato yields by an average of 10.2—37.9% compared with untreated plots. The application of combinations of BT biological insecticides during the growing season helped to control the Colorado potato beetle and preserve the yield. The best protection was provided by a bioinsecticide treatment regime comprising four consecutive applications: the first — Bitoxibacillin BT, SC, 3.0 l/ha, the second — Boverin BT, SC, 10.0 l/ha, the third — Actofit BT, SC, 3.0 l/ha, the fourth — Metarizin BT, SC, 3.0 l/ha.